Investigation of progress of reactions and evolution of radial heterogeneity in the initial stage of thermal stabilization of PAN precursor fibres. (March 2016) - Nunna, Srinivas; Naebe, Minoo; Hameed, Nishar; Creighton, Claudia; Naghashian, Sahar; Jennings, Matthew J.; Atkiss, Stephen; Setty, Mohan; Fox, Bronwyn L.
Abstract: The relationship between process parameters and structural transformations in the fibres at each stage of the carbon fibre manufacturing process play a crucial role in developing high performance carbon fibres. Here we report a systematic method which uses the combination of Taguchi approach and scientific evaluation techniques to establish these relationships for the initial stage of thermal stabilization. Density, cyclization index and fraction of reacted nitriles of a precursor containing acrylonitrile, methacrylate and itaconic acid (AN/MA/IA) were used to assess the progress of stabilization in the fibres with respect to various combinations of process parameters. The extent of progress of stabilization improved with increase in temperature (from 225 to 235 °C) and time (from 12 to 24 min) whereas an opposite trend was observed with increase in the tension on the fibres from (1600–2550 cN). According to optical microscopy, radial heterogeneity was observed in the fibres treated at 235 °C. Interestingly, we were able to identify the existence of heterogeneous modulus distribution from skin to core of the precursor fibres which was further transferred to treated fibres. The overall radial modulus of treated fibres was higher than the precursor fibres. In contrast to the literature, the fracture morphology of the fibre samples indicated that initiation of crack is caused by surface defects rather than radial heterogeneity.